1992
DOI: 10.1037/0022-3514.62.6.934
|View full text |Cite
|
Sign up to set email alerts
|

What young people want to know when: Effects of mastery and ability goals on interest in different kinds of social comparisons.

Abstract: Integrating developments in social comparison and achievement theories suggested that ability goals will promote ability-appraisal and self-serving functions of social comparison and that mastery goals will enhance interest in social comparisons that can promote learning. A novel design let Ss choose between different kinds of social information. Seventy-eight Israeli 6th graders performed a task in a mastery or ability goal condition and then examined tables providing social information relevant to learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
181
1
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 56 publications
18
181
1
5
Order By: Relevance
“…This is because although adoption of mastery goals yielded higher levels of competence than performance goals in conditions of unfavourable social comparisons, at the same time, unfavourable social comparisons yielded lower perceptions of competence than favourable social comparisons for mastery-oriented students. Notably, previous experimental research could not ascertain the magnitude of the "mastery goal advantage" effect either because they did not observe it (Van Yperen & Leander, 2014) or because they did not induce both favourable or unfavourable social comparisons in the same study (Butler, 1992(Butler, , 1993Darnon, Dompnier, Gillieron, & Buttera, 2010;Regner, Escribe, & Duperyat, 2007). In a way, therefore, results of the current study show that the social comparison effect observed in previous research is stronger than previously thought in that it is not eliminated by masteryoriented students' tendency to respond positively to unfavourable social comparisons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because although adoption of mastery goals yielded higher levels of competence than performance goals in conditions of unfavourable social comparisons, at the same time, unfavourable social comparisons yielded lower perceptions of competence than favourable social comparisons for mastery-oriented students. Notably, previous experimental research could not ascertain the magnitude of the "mastery goal advantage" effect either because they did not observe it (Van Yperen & Leander, 2014) or because they did not induce both favourable or unfavourable social comparisons in the same study (Butler, 1992(Butler, , 1993Darnon, Dompnier, Gillieron, & Buttera, 2010;Regner, Escribe, & Duperyat, 2007). In a way, therefore, results of the current study show that the social comparison effect observed in previous research is stronger than previously thought in that it is not eliminated by masteryoriented students' tendency to respond positively to unfavourable social comparisons.…”
mentioning
confidence: 99%
“…According to theory, people are concerned with social comparison when they pursue performance-approach goals and not when they pursue mastery-approach goals. Recently, however, a number of studies have documented that mastery-oriented students are not completely oblivious to normative information pertaining to classmates' grades (Butler, 1992(Butler, , 1993Darnon, Dompnier, Gillieron, & Buttera, 2010;Regner, Escribe, & Duperyat, 2007). Specifically, in a series of experimental studies conducted in educational contexts, Butler (1993) showed that students who were instructed to adopt mastery goals exhibited a marked interest in normative information pertaining to other students' grades.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, as evidenced by prior research showing other psychosocial variables such as self-efficacy, achievement goals, and perceived control to moderate the effects of social comparisons (e.g., Butler, 1992;Buunk et al, 1990;Lockwood et al, 2004), it is possible that similar moderation effects may account for the mixed effects observed (e.g., downward comparisons). Additionally, further examination of the moderating effects of additional variables not explored in this study, such as school culture, cohort effects, leadership style, and personality-related factors, could also help to ascertain how and when these effects occur in real-world teaching contexts.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…According to Festinger (1954), individuals seek out information about others primarily to facilitate accurate self-evaluation (Suls et al, 2002;Taylor & Lobel, 1989), with the resulting contrasts leading to specific psychological and behavioral consequences (e.g., affect : Smith, 2000;White, Langer, Yariv, & Welch, 2006;motivation: Bailis, Chipperfield, & Perry, 2005;achievement, Blanton, Buunk, Gibbons, & Kuyper, 1999). Nevertheless, research in this domain also highlights the importance of individual differences and demographic factors in social comparisons processes (e.g., achievement goal orientation, Butler, 1992;emotions, Lyubomirsky, & Ross, 1997;self-construal, Stapel & Koomen, 2001; employment status, Sheeran, Abrams, & Orbell, 1995).…”
Section: Social Comparison Processesmentioning
confidence: 99%
“…To start with, projects often allow for the improvement of individuals' learning (Dweck 1986) and generate mastery over feelings (Butler 1992). In turn, these feelings demonstrate the generation of competence (Rawsthorne and Elliot 1999).…”
Section: Project Failure Need For Competence and Negative Emotionsmentioning
confidence: 99%